Effect of Transplanting Dates and Spacing on Yield Attributing Character, Productivity and Economics of Potato Cultivation Through True Potato Seed (TPS) Technology - Debashish Sen; Amitava Rakshit; Narayan Chandra Sarkar; Dulal Chandra Ghosh; Subir Kumar Bardhan Roy (Italian Journal of Agronomy)
A field experiment in split plot design was conducted during the rabi season of 2001-02 and 2002-03 at Potato Research and Seed Multiplication Farm, Anandapur,West Midnapore,West Bengal to study the effect of dates of transplanting and spacing on yield attributing character, productivity and economics of potato cultivation through true potato seed (TPS) technology. The highest number of tubers per plant was recorded in early transplanted (December 3) crop, while, crop spacing did not produce any significant differences in recording tuber number per plant. Early established crop also produced significantly higher tuber weight per plant as compared to intermediate (December 11) and late (December 19) transplanted crops and widely spaced (60 x 15 cm) crop recorded higher weight of tuber per plant as compared to the narrowly spaced crop. Early transplanting and wider spacing also showed its superiority in respect of recording harvest index of potato. As such, early transplanted and densely planted crops produced significantly higher yield of seedling tuber, marketable tuber and total tuber than their counterparts. Though cost of production of early transplanted and closely spaced crop was higher, but net profit and return per rupee investment was also higher in those cases.